HUBUNGAN ASUPAN ZAT GIZI MAKRO TERHADAP KEBUGARAN ATLET MARCHING BAND DI PELATDA ATLET PON BANTEN 2016 - Kuswary, Mury (Jurnal Nutrire Diaita (Ilmu Gizi), 2016)
AbstractThe purpose of this study was to analyze the effect of the frequency of moderate-intensity aerobic exercise on body fat of the members AeroFun Aerobic at Esa Unggul University. This study was using a quasi experimental design with sample of 21 students then given intervention by performing moderate-intensity aerobic exercise for 8 weeks. This intervention was done one time per week. Primary data including bodyweight, body mass index (BMI) and body fat percentage before and after treatment. Results of t-tests showed the respondents there is a significant decrease before and after treatment on percentage of body fat (p<0.05) while the weight and BMI were not significant (P>0.05). Keywords: Fitness, nutritional status, athletes. AbstrakTujuan penelitian adalah untuk menganalisis hubungan hubunganasupanzat gizi makro terhadap kebugaranatlet marchingband di Pelatda atlet PON Banten 2016. Penelitian ini menggunakan desain cross sectional dengan subjek berjumlah 24 responden. Hasil uji t-tes menunjukkan pada responden menunjukkan tidak terdapat hubungan yang sigifikan antara IMT dan asupan zat gizi makro terhadap kebugaran tubuh (p<0.05). Kata kunci: Kebugaran, status gizi, atlet